2008
DOI: 10.1002/pd.1945
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of fetal cardiac evaluation with magnetic resonance imaging: preliminary experience

Abstract: Our preliminary experience demonstrates the feasibility to visualize the fetal heart with routine fetal MRI protocols in particular, by means of acquisition of TrueFISP imaging (morphological study) and real-time cine-MRI (dynamic study), potentially making MRI a second-level tool to add to fetal echocardiography in the prenatal study of congenital cardiac malformations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 29 publications
3
43
1
Order By: Relevance
“…Due to its noninvasive nature, this present study is far more practicable, particularly in relation to human subjects. Compared with images of prior studies (17)(18)(19), the visualization in this study of the aforementioned anatomical structures demonstrated considerable improvements in the adequacy of the visualization. Prior studies described difficulties with the imaging of main cardiac outflow vessels, such as the aorta with its valve (19).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Due to its noninvasive nature, this present study is far more practicable, particularly in relation to human subjects. Compared with images of prior studies (17)(18)(19), the visualization in this study of the aforementioned anatomical structures demonstrated considerable improvements in the adequacy of the visualization. Prior studies described difficulties with the imaging of main cardiac outflow vessels, such as the aorta with its valve (19).…”
Section: Discussionmentioning
confidence: 86%
“…Compared with images of prior studies (17)(18)(19), the visualization in this study of the aforementioned anatomical structures demonstrated considerable improvements in the adequacy of the visualization. Prior studies described difficulties with the imaging of main cardiac outflow vessels, such as the aorta with its valve (19). In contrast to such studies, the current study enabled the aortic valve to be visualized, both in open and in closed condition, using the novel triggering method (Fig.…”
Section: Discussionmentioning
confidence: 86%
“…According to a report of 32 fetuses assessed for congenital heart disease, fetal MRI permitted identification of extracardiac anomalies associated with cardiac abnormalities. The authors document that MRI detected adjunctive fetal anomalies (particularly in CNS and neck) that US did not depict (Manganaro et al, 2008).…”
Section: Fetal Cmr Findings In Complex Congenital Heart Disease (Chd)mentioning
confidence: 99%
“…In-utero MR imaging of the fetal heart 2.2.1 Feasibility and patients' selection MRI of the fetal heart is feasible (Saleem, 2008); however, it has not been thoroughly investigated with only few reports in literature most of them in the form of case reports or preliminary experiences (Gorincour et al, 2007;Kivelitz et al, 2004;Manganaro et al, 2008). We will depend in discussion of MRI of fetal heart in this chapter on findings from our study of 298 pregnancies at high risk for CHD that were enrolled sequentially from September 2003 to August 2010 in our institutional review board-approved study.…”
Section: 2mentioning
confidence: 99%
“…Delayed myocardial enhancement magnetic resonance can serve to delineate the location and transmural extent of endocardial fibroelastosis in infants, thus providing an accurate roadmap for the surgical planning of fibroelastosis resection and for monitoring the results . Magnetic resonance is also proposed to aid fetal ultrasonography in the prenatal assessment of congenital cardiac malformations (Manganaro et al, 2008).…”
Section: Magnetic Resonancementioning
confidence: 99%